Talak Via WhatsApp dalam Perspektif Mazhab Syafi’i dan Maliki: Studi Komparatif tentang Keabsahan dan Implikasinya - Fithoroini, Dayan (Posita: Jurnal Hukum Keluarga Islam, 2025)
This study provides a comprehensive analysis of the differing approaches between Shafi'i and Maliki schools of thought regarding digital talaq, with particular focus on modern communication platforms like WhatsApp. Employing qualitative research methods through textual analysis of classical fiqh books and contemporary fatwas, the research reveals paradigmatic differences between these two schools. The findings indicate that while the Shafi'i school recognizes digital talaq as a contemporary form of written divorce (kitabah) emphasizing clear intent and message substance, the Maliki school maintains strict formal requirements including witnesses and identity verification. The study highlights the dilemma between legal flexibility and sharia certainty, where the Shafi'i's adaptive approach may create interpretive ambiguity, while Maliki's rigidity potentially limits justice access for marginalized communities.